Efektivitas Konsentrasi Ekstrak Patikan Kerbau (Euporbhia hirta L. ) Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Budiarti, Retni (Universitas Jambi, 2012)
Some groups of traditional people in Indonesia use patikan kerbau to treat various diseasesincluding gastrointestinal disease and eczema. Both disease are caused by the bacterium ofStaphylococcus aureus. The lack of empirical data about the efficacy pf the plant urges the need toinvestigate the bioactivity of the plant. This research concludes that the extract of patikan kerbauinhibits the growth of S.aureus at the effective concentration 500 ppm.